Real-world scenario of retinopathy of prematurity in Kerala - Anubhav Goyal; A Giridhar; Mahesh Gopalakrishnan (Kerala Journal of Ophthalmology, 2017)
Objective: The objective was to study the incidence and risk factors predisposing to retinopathy of prematurity (ROP) and to assess the outcome after laser photocoagulation. Design: This was a retrospective cohort observational study. Materials and Methods: Infants admitted to a Neonatal Intensive Care Unit of 12 referral hospitals in Kerala between May 2015 and June 2016 were followed up till retinal vascularization completes. Preterm infants with birth weight <1700 g and gestation> 34 weeks were screened for ROP at 4 weeks after birth or 31–33 postconceptional age, whichever was later. Infants with birth weight> 1700 g and gestation> 35 weeks were screened only on neonatologist's discretion. All infants were screened according to the Indian guidelines of type 1 and 2 ROP. We treated both eyes of all infants showing threshold ROP. Statistical analysis was done using SPSS version 16 (SPSS Inc., Chicago, IL, USA). Results: The incidence of ROP in 622 infants screened was 158 (25.4%), of which threshold ROP was seen in 61 (9.80%). No ROP was found in infants weighing> 2000 g or with a gestational age> 36 weeks. Risk factors predisposing to ROP were hours on ventilator, hemoglobin%, oxygen therapy, and number of blood transfusions, which were more significant in infants with type 1 or threshold ROP than type 2 ROP. Out of 97 infants with type 2 ROP, we saw stage 1 in 31 (30.92%), stage 2 in 59 (60.82%), and stage 3 in 7 (7.21%) infants. 61 (9.80%) infants with threshold ROP were treated with laser photocoagulation. Aggressive posterior ROP or rush disease was seen in 29 (47.54%) of 61 infants with type 1 ROP. Only 2 (3.27%) infants showed falciform fold over macula and 1 (1.63%) infant was blind due to retinal detachment. Conclusion: One-fourth of the infants showed ROP, of which one-tenth needed laser photocoagulation, the outcome of which was good. Risk factors predisposing to ROP were low hemoglobin, high oxygen therapy, increased number of blood transfusions, and hours of ventilator.